FIRST RESULTS OF MAGNETOTELLURIC SOUNDINGS FOR MAPPING THE RIPHEAN SEDIMENTS OF THE BAIKAL FOREDEEP - A. V. Pospeev; I. K. Seminskiy; D. B. Nemtseva (Геодинамика и тектонофизика)
The article presents the first results of magnetotelluric sounding (MTS) surveys of the Baikal foredeep. This study is part of the project of the Institute of the Earth’s Crust SB RAS, which investigates the geological and geoelectrical structure of the southeastern marginal part of the Siberian platform and updates the model of the Baikal rift zone. An objective is to preliminary assess the mining potential of the Riphean strata in the Baikal foredeep. The relevance of the study centers on the possibility of discovering a new promising oil-gas field in proximity to energy-intensive industrial and agricultural enterprises. The MTS section of the sedimentary cover shows an increased conductivity of its lower part, which is most likely due to highly porous carbonate-terrigenous rocks in the middle – lower part of the ‘Baikal three-member’ structure. The intra-lithospheric conductive layer that hosts most of the earthquake hypocenters of the Baikal rift is investigated.